ONLINE-COURSE DEVELOPMENT VIA DISCUSSION-FORUM ON THE STUDENTS OF PHYSIC EDUCATION UNIVERSITAS NEGERI SEMARANG - Sudarwati, I.; Khanafiyah, S.; Sugiyanto, S. (Jurnal Pendidikan Fisika Indonesia, 2017)
Students of Physic Education of Universitas Negeri Semarang often find some difficulties to understand the material. During difficult times, students usually find references on the internet,ask a friend who already understand, or ask a senior friend. Mostly students have a device that can be used to access the internet. Online-course via discussion-forum can be used as a discussion facility when they find difficulties to understand. Online-course via discussion-forum developed with ADDIE development models that includes the stages of analysis, design, development, implementation, and evaluation. Online-course discussion forum contains the list of courses that can be accessed by students via internet through the website discussion.belajarfisika.web.id. Feasibility of online course discussion forum was measured through assessment sheets of feasibility test from validators and questionnaire responses from students. The results of the feasibility test from the validator and student responses indicate that criteria are eligible. Results of the questionnaire about students perceptions of learning through online course discussion forum show that Physic Education Students of Universitas Negeri Semarang have good perceptions of learning through online-course via discussion-forums.